The Influence of Islamic Religious Education Instruction on the Social Attitudes of Grade VIII Students at MTs Al-Ikhlas Proklamasi Karawang - Nurjamilah Azizah; Jaenal Abidin; Tajuddin Nur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic Religious Education Learning is a planned interaction process between educators and students to transfer and instill Islamic teachings sourced from the Qur'an and Hadith. While social attitudes are a person's tendency to respond to social situations, the environment, or other individuals in a certain way, either positively or negatively. This study aims to see whether there is an influence between Islamic Religious Education Learning on the Social Attitudes of Students in Class VIII MTs Al-Ikhlas Proklamasi Karawang. This study uses a quantitative approach with a correlational method and is a field research. The researcher's sample consisted of 54 students in class VIII MTs Al-Ikhlas Proklamasi Karawang. The results showed that 35 students (64.8%) were in the moderate category related to Islamic religious education learning. The social attitudes of students showed 41 people (75.92%) in the moderate category. The results of t count 5.886> t table 0.2000. The results of simple linear regression showed Y=29.859+0.654X. This means that every one unit increase in Islamic religious education learning increases students' social attitudes by 0.654 units. The significance test yields 0.000<0.05. So Ha is accepted and Ho is rejected. The R Square value of 0.723 indicates 72.3% of the influence of Islamic religious education learning on students' social attitudes in class VIII MTs Al-Ikhlas Prokalamasi Karawang.